A Case of Ocular Defect: Prosthetic Rehabilitation with Semi Customized Prosthesis - Rahman, Md Rezaur; Tariquzzaman, Md; Ali Hyder, Md Liakat; Rab, Md Abdur; Mohiuddin Chowdhury, Golam (Journal of Armed Forces Medical College, Bangladesh, 2022)
Facial defect rehabilitation is a challenging task. Individualized technique is required for each patient to accomplish the task. Due to any cause loss of an eye with disfigurement of face makes severe physical and psychological distress. A 65-year-old male Patient complaint with missing left eye was referred to the Department of Prosthodontics, Military Dental Centre Dhaka for artificial eye replacement. A defect with compressed orbit and unharmed tissue bed was found by clinical examination. Mode of rehabilitation for the missing eye is ocular prosthesis. Here I tried to describe a simple technique for the fabrication of ocular prosthesis. With stock iris and customized sclera, we have fabricated a semi customized ocular prosthesis. It provides very good result functionally and esthetically. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 95-98